2018
DOI: 10.3311/ppci.12173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Content on the Mechanical Parameters of the Intact Rock and Rock Mass

Abstract: The goal of this paper is to present the influence of the water saturation of the intact rock on different mechanical parameters, such as internal friction angle, cohesion, Hoek-Brown constant (mi ). Analyzing the previously published results, it was found that due to water saturation both the uniaxial compressive strength and tensile strength decrease similarly, i.e. the ratio of these two values is constant, thus the internal friction angle does not change but only the cohesion. Likewise, Hoek-Brown constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The fact that in R-1 and R-2 the percentages of reduction of cpeak were found to be much greater than the percentages of reduction of ϕpeak suggests that the reduction of cohesion could be considered the controlling factor for the observed peak strength decreases in these stone types. This result would be in line with the theoretical analysis performed by Vásárhelyi and Davarpanah [75] who suggested that friction angle is an intrinsic parameter of the rock which is not influenced by the moisture content. The cpeak losses found in the three calcarenites could be attributed to physicochemical processes such as the…”
Section: Impact Of Water On Mohr-coulomb and Hoek-brown Shear Strength Parameterssupporting
confidence: 91%
“…The fact that in R-1 and R-2 the percentages of reduction of cpeak were found to be much greater than the percentages of reduction of ϕpeak suggests that the reduction of cohesion could be considered the controlling factor for the observed peak strength decreases in these stone types. This result would be in line with the theoretical analysis performed by Vásárhelyi and Davarpanah [75] who suggested that friction angle is an intrinsic parameter of the rock which is not influenced by the moisture content. The cpeak losses found in the three calcarenites could be attributed to physicochemical processes such as the…”
Section: Impact Of Water On Mohr-coulomb and Hoek-brown Shear Strength Parameterssupporting
confidence: 91%
“…water content (see e.g. [18] or heating cycles [19], among the others. Recently, Vásárhelyi et al [20] analyzed the Hoek-Brown equation and suggested minor modification of it for Hungarian granitic rocks.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, for a more precise and fundamental description of the mechanical behaviour of rock, one should apply non-equilibrium continuum thermodynamics along the lines of Asszonyi et al [23,25] and beyond. These relationships can be used for determining the mechanical parameters of the rock mass, as well [24,26].…”
Section: Relationship Between CImentioning
confidence: 99%